Acute Antioxidant Response to Two Types of Exercises: 2000 M Run vs. Burpee Test - Lucrecia Carrera-Quintanar; Lorena Funes; María Herranz-López; Néstor Vicente-Salar; Juan Mielgo-Ayuso; Manuel Moya-Ramón; Antoni Pons; Vicente Micol; Enrique Roche (MDPI AG, 2024)
Physical activity results in oxidative stress, as evidenced by the increased production of reactive oxygen, nitrogen species, and inflammatory mediators. The management of these components is instrumental for antioxidant adaptation to exercise and post-exercise recovery. Therefore, the present report aims to study the antioxidant response to two types of exercise (a 2000 m run and a burpee test) in healthy volunteers after a long period of inactivity (1-2 months). Antioxidant enzyme activities and oxidative stress markers (protein carbonyls and malondialdehyde content) were measured in neutrophils, peripheral blood mononuclear cells, and plasma. These parameters were determined under basal conditions and immediately post-exercise. Compared to those in basal state, neutrophil superoxide dismutase (28.3 vs. 22.9 pkat/109 cells), glutathione peroxidase (147.5 vs. 120.1 nkat/109 cells), and catalase (106.3 vs. 57.9 k/109 cells) were activated significantly (p < 0.05) after the burpee test. Peripheral blood mononuclear cells exhibited only significant (p < 0.05) catalase activation (113.6 vs. 89.4 k/109 cells) after the burpee test. Other enzymes, such as glutathione reductase and myeloperoxidase, tended to increase post-exercise, although the differences from baseline were not significant. Finally, compared to basal conditions, the protein carbonyl (24.5 vs. 14.5 mmol/L) and malondialdehyde (39.6 vs. 18.3 mmol/L) contents increased significantly (p < 0.05) in neutrophils and in plasma (115.1 vs. 97.8 and 130.2 vs. 123.4 μmol/L, respectively) after the burpee test. In conclusion, high-intensity exercise seems to induce immediate oxidative stress in inactive individuals, and the acute antioxidant response was slightly greater after the burpee test than after the 2000 m run. Glutathione-dependent antioxidant systems are activated immediately as protective mechanisms.